(untitled) (Universal International Scientific Journal, 2026)
In this article, small businesses are presented as the most flexible and active part of the economic system in a market economy. They play an important role in increasing employment, creating new sources of income, and supporting regional development. Therefore, a scientific assessment of their activities is of particular importance in economic policy and management decisions.